Professional Competencies and Female Integration in service companies in Metropolitan Lima - Bocanegra Carrero, Antuanett Margarita; Huancaruna Montoya, Luz Claribel; Méndez Gutiérrez, Leidy Lucia (LACCEI, 2024)
This scientific article delves into the labor market integration of women in service sector companies in Metropolitan Lima for 2024, exploring the relationship between professional skills and their inclusion. It is evidenced that competencies, although crucial, do not automatically guarantee women higher-responsibility roles. It also underscores the need for inclusive labor policies and educational programs to enhance female employability, prompting reflection on overcoming structural barriers perpetuating gender inequality in the workplace. Romero’s theory emphasizes employability and occupational opportunities: the former pertains to available job opportunities, while the latter encompasses individual skills to seize those opportunities. This highlights the importance of aligning skills with labor market demands to facilitate effective and sustainable integration. In conclusion, while competencies are necessary, they are insufficient to ensure women’s integration into higher-responsibility roles. The study reveals a moderate correlation between professional competencies and female integration, identifying other key variables such as inclusive organizational policies and governmental support for gender equality. Achieving true equal opportunities requires addressing these complementary variables and creating work environments that promote diversity and equity.